Herpes simplex virus 1 rhombencephalitis in a patient with chromosomally integrated human herpesvirus-6A. (2020) - Silva, Raquel; Duque, Vitor; Magano, Rita; Trindade, Luís
Abstract: Central nervous system infection caused by Herpes simplex virus 1 remains a significant cause of morbidity and mortality in transplant patients. Additionally, the clinical implications of the recently discovered Human herpesvirus 6A are still under investigation. Hereby, we report a clinical case of an immunosuppressed patient following kidney transplantation and with chromosomally integrated human herpesvirus-6A (CIHHV-6A) that developed rhombencephalitis due to herpes virus simplex 1. This case highlights the importance of investigating the CIHHV-6 status in the differential diagnosis whenever a human herpesvirus is detected in the cerebrospinal fluid.